Peran Promo Shopee (Cashback dan Gratis Ongkir) dalam Membangun Loyalitas Pengguna di Kalangan Mahasiswa Gen Z Kota Tebing Tinggi - Dewi, Kumala Vera; Siregar, Raysal Januar; Wibowo, Muhammad Arif (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
The use of e-commerce is increasing among the younger generation, especially Generation Z students who are known to be responsive to promos and attractive offers. Shopee as one of the most popular e-commerce platforms offers cashback and free shipping promos to attract and retain customers. This study aims to determine the effect of cashback and free shipping promos on Shopee user loyalty among Gen Z students in Tebing Tinggi City. The method used is a quantitative approach with a survey technique through a questionnaire. This study uses the Cochran formula for sampling because the population is too large and unknown, so that a research sample of 96 respondents was obtained. The sample selection method in the study uses probability sampling methods. The results of the study show that there is a significant influence between cashback promos on Shopee user loyalty, there is a significant influence between free shipping promos on Shopee user loyalty, and cashback and free shipping promos together affect Shopee user loyalty.